The Role of Arts in Identity Formation and Collective Memory in The Digital age - Melianto, Donny; Syamsudin, Ahmad (MSJ : Majority Science Journal, 2024)
The role of art in the formation of identity and collective memory in the digital era is becoming an increasingly relevant topic along with the rapid advancement of technology and digital media. In this context, art is not only a medium for individual expression, but also an important means of forming a collective memory that connects people in a community or nation. With the emergence of digital platforms, art has the potential to change the way people build, communicate, and maintain their identities. This journal examines how art, whether in the form of visuals, music, or other art forms, influences the formation of social identity and collective memory in the digital era, through the approach of communication theory and cultural studies. As part of this study, using the Systematic Literature Review (SLR) method, this journal focuses on analyzing various literatures that discuss the relationship between art, identity, and collective memory in the digital context. This study also looks at how social media, digital art platforms, and other multimedia technologies play a role in strengthening or redefining people's collective memory and identity. The results of this study indicate that digital art plays an important role in mediating the process of identity formation, both at the personal and collective levels, and influences the way the digital generation remembers and responds to their history and culture.